2005
DOI: 10.1007/s00013-005-1385-z
|View full text |Cite
|
Sign up to set email alerts
|

On the radical of a monomial ideal

Abstract: Algebraic and combinatorial properties of a monomial ideal and its radical are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 11 publications
4
54
0
Order By: Relevance
“…Assume that R is normal and I ⊂ R is a (not necessarily monomial) ideal. In §6, generalizing a result of Herzog, Takayama and Terai [9] [20] showed that the range…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Assume that R is normal and I ⊂ R is a (not necessarily monomial) ideal. In §6, generalizing a result of Herzog, Takayama and Terai [9] [20] showed that the range…”
Section: Introductionmentioning
confidence: 76%
“…But the next theorem states that if √ I is a monomial ideal then such an example does not exist. When R is a polynomial ring, this result was obtained in [9]. To extend Proposition 7.4 to semigroup rings, we have to introduce the notion supp + (u) for u ∈ R d .…”
Section: Ideals Whose Radicals Are Monomial Idealsmentioning
confidence: 98%
“…Thus the questions discussed in this paper can be specified as follows: For which squarefree Cohen-Macaulay monomial ideals does there exist at least one nontrivial Cohen-Macaulay modification, or do exist infinitely many nontrivial CohenMacaulay modifications, and for which Cohen-Macaulay monomial ideals I are all monomial ideals J ∈ G I or J ∈ F I CohenMacaulay? Related questions have been studied in [4,1].…”
Section: Macaulay Monomial Ideal In Smentioning
confidence: 99%
“…It is well known that depth S/I ≤ depth S/ √ I (see the proof of [8,Theorem 2.6]) and equivalently depth I ≤ depth √ I. The first inequality holds also for sdepth, that is sdepth S/I ≤ sdepth S/ √ I (see [2,Theorem 1]).…”
Section: Introductionmentioning
confidence: 99%